Effect of Intestinal Atrophy and Hepatic Impairment Induced by Parenteral Nutrition on Drug Absorption and Disposition in Rats. (February 2015) - Fukushima, Keizo; Miki, Takahiro; Nakamoto, Kazuo; Nishimura, Asako; Koyama, Hikaru; Ichikawa, Hideki; Shibata, Nobuhito; Tokuyama, Shogo; Sugioka, Nobuyuki
Background : Long-term parenteral nutrition (PN) has a high risk of hepatic dysfunction and intestinal atrophy. The present study investigated the effect of PN-induced intestinal atrophy and hepatic impairment on drug pharmacokinetics by using 2 contrasting compounds: phenolsulfonphthalein (PSP) and cyclosporin A (CyA). Materials and Methods : PSP or CyA was administered to 7-day PN-fed Rats (PN rats) and sham operated rats (control rats) via intravenous (IV) or intraloop administration of the intestine. Pharmacokinetic parameters with 2-compartment analysis including area under the concentration vs time curve (AUC) and the permeability after in situ intraloop administration ( P loop ) were obtained from both concentration profiles after different administration routes. Results : After IV administration of PSP to control and PN rats, there was no notable difference in any of the pharmacokinetic parameters. In contrast, after intraloop administration, AUC and P loop in PN rats were approximately 2.6- and 2.0-fold higher than that in control rats, respectively. On the other hand, after IV administration of CyA, the terminal half-life and total body clearance were prolonged and decreased in PN rats, respectively, resulting in 2.0-fold increase in AUC. After intraloop administration, the AUC of PN rats was increased to approximately 1.3-fold that of control rats, whereas no notable difference was observed in P loop . Conclusion : The intestinal permeability of PSP was enhanced by intestinal atrophy induced by PN, while the metabolism of CyA was diminished by hepatic impairment by PN. These results revealed the physicochemical property-based pharmacokinetic alterations during PN; for a more detailed understanding, however, further studies are needed.